2016
DOI: 10.1208/s12249-016-0516-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Modeling and Physicochemical Properties of Supramolecular Complexes of Limonene with α- and β-Cyclodextrins

Abstract: This study evaluated three different methods for the formation of an inclusion complex between alpha- and beta-cyclodextrin (α- and β-CD) and limonene (LIM) with the goal of improving the physicochemical properties of limonene. The study samples were prepared through physical mixing (PM), paste complexation (PC), and slurry complexation (SC) methods in the molar ratio of 1:1 (cyclodextrin:limonene). The complexes prepared were evaluated with thermogravimetry/derivate thermogravimetry, infrared spectroscopy, X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 35 publications
3
5
0
Order By: Relevance
“…The TGA-DSC curve of β-CD was consistent with findings from previous studies ( Figure 1(D,E) ) (Dos Passos Menezes et al. 2017 ). The rapid decline in the DSC curve near 330 °C indicated the decomposition of water ( Figure 1(E) ).…”
Section: Resultssupporting
confidence: 91%
“…The TGA-DSC curve of β-CD was consistent with findings from previous studies ( Figure 1(D,E) ) (Dos Passos Menezes et al. 2017 ). The rapid decline in the DSC curve near 330 °C indicated the decomposition of water ( Figure 1(E) ).…”
Section: Resultssupporting
confidence: 91%
“…It was observed that only partial complexation was obtained, with non-complete formation of 1:1 inclusion complexes. Limonene-β-CD complex seems to be slightly more stable than limonene-α-CD with binding energies of −4.54 kcal and −4.05 Kcal, respectively [124]. A similar trend was observed by Astray et al who determined the binding constant of limonene-(α/β)-CDs complex formation by UV-Vis technique coupled with molecular mechanics' calculations [125].…”
Section: Cyclodextrinssupporting
confidence: 60%
“…D-limonene (DL) (Figure 1), is an alcoholic monoterpene and the major constituent of the essential oil extracted from citrus species such as lemon, lime and orange. 7 Previous studies have demonstrated that DL has low toxicity and presents antioxidant, 8,9 vasodilatation, 10,11 and antihypertensive proprieties. 12 The effect of DL on the heart has not yet been elucidated and investigations into its action mechanism can provide new insights about DL and the cardiovascular system.…”
Section: Introductionmentioning
confidence: 99%